2013
DOI: 10.1017/s0001924000008654
|View full text |Cite
|
Sign up to set email alerts
|

In-flight simulation of wake encounters using deformed vortices

Abstract: During the decay process the shape of wake vortices changes significantly which has an influence on the encounter characteristics, hence on the encounter hazard. In order to evaluate the influence of vortex deformation on the wake encounter hazard, in-flight simulations with the DLR research aircraft ATTAS were carried out. For a realistic analysis of wake encounters flow fields of matured vortices were generated with large eddy simulations. These flow fields were used for the determination of histories of ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…This method was deemed feasible by Barrows [23], verified against wind tunnel tests by de Bruin [24], and further validated using real flight test data by Fischenberg [25] and Jategaonkar [26]. The method was applied in various studies in the past [27][28][29][30][31][32] and is accepted to provide vortex induced forces and moments of acceptable accuracy.…”
Section: B Implementation Of Vortex Flow Fields In the Aircraft Simumentioning
confidence: 97%
“…This method was deemed feasible by Barrows [23], verified against wind tunnel tests by de Bruin [24], and further validated using real flight test data by Fischenberg [25] and Jategaonkar [26]. The method was applied in various studies in the past [27][28][29][30][31][32] and is accepted to provide vortex induced forces and moments of acceptable accuracy.…”
Section: B Implementation Of Vortex Flow Fields In the Aircraft Simumentioning
confidence: 97%
“…The method was applied in various studies in the past [33,[38][39][40] and is accepted to provide vortex induced forces and moments of acceptable accuracy.…”
Section: B Implementation Of Vortex Flowfields In the Aircraft Simulmentioning
confidence: 99%
“…For pilot-in-the-loop investigations with subjective pilot ratings as well as for offline simulation studies, jRCRj max has proven to be a suitable metric. Past studies showed that pilots accepted encounters below jRCRj max of 0.2 [38,39] during approach but out of ground effect. Below this value, the impact of the wake was not distinguishable from natural atmospheric turbulence.…”
Section: Severity Assessmentmentioning
confidence: 99%
“…In addition, the uncertainties in vortex modeling, i. e. whether to include wake deformation in safety assessments or to use a simple straight vortex pair, are assumed to be larger than the inaccuracies of highly sophisticated aircraft flight simulation models. Aircraft encounters with wavy vortices and vortex rings have been analyzed by means of offline simulations 12,13 and piloted tests in certified training and research flight simulators 14,15 or by in-flight simulation, 16 using either simplified models of the deformed vortices or three-dimensional fields of vortex-induced velocities from prior Large-Eddy Simulation (LES). Those studies indicate a reduced encounter severity for the vortex ring phase after linking.…”
Section: Straight Vorticesmentioning
confidence: 99%